Payakumbuh: Kajian Arkeologi Perkotaan di Keresidenan Pantai Barat Sumatra - Sandy, Dwi Kurnia (Badan Riset dan Inovasi Nasional (BRIN), 2025)
Payakumbuh is one of the colonial cities developed by the Netherland East Indies Government in the Residency Sumatra’s Westkust. This research aims to explain the history of Payakumbuh's development since it was established as the Capital of Afdeeling Limapuluh Kota until the influence of the colonial urban planning concept on its modern spatial development. The method used in this research is a desk study, with data collection from maps, photos, newspapers, and related documents from colonial era, which are then verified through field surveys. The results revealed five main types of infrastructure built in Payakumbuh during the colonial period, reflecting the city's function as an administrative and trading centre. The urban planning of Payakumbuh at that time was divided into three main zones: the core zone that functioned as the centre of government and trade, the buffer zone that included community service facilities and the local community settlement zone located on the outskirts of the city. The current development of Payakumbuh shows spatial adaptation that retains some colonial elements, but with functions that have been adjusted to modern needs. This research concludes that the Netherland East Indies colonial concept of urban planning has a significant influence on the development of Payakumbuh City until today.